Oralność tekstów Jana Kochanowskiego - Data, Krystyna (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
The subject matter of the article is defining the terms ‘orality’ and ‘spoken language’. The author assumes that these notions apply to two different concepts. The dissimilarity between ‘orality’ and ‘spoken language’ is analysed with reference to the examples taken from Jan Kochanowski’s works, and is particularly reflected in vocabulary, linguistic strategies, punctuations and text composition. The first term should be identified with the rules of rhetoric and the latter with a variety of colloquial expressions.
Keywords: oralność; Jan Kochanowski; oralność prymarna; oralność wtórna